Biological control and cross infection of the Neofusicoccum spp. causing mango postharvest rots in Spain. - Guirado-Manzano, Lucía; Tienda Serrano, Sandra; Guirado, Emilio; Sarmiento, David; De-Vicente-Moreno, Antonio; Cazorla-López, Francisco Manuel; Arrebola-Díez, Eva María (My University, 2024)
Mango and avocado are the main subtropical crops in southern Spain. These fruits are grown and processed in the same geographical area and are transported to the rest of Europe. However, postharvest diseases during transportation and storage could damage the export market. These two fruits share, on many occasions, farms, processing and even transport, and could act as cross inoculation source. In this work, symptoms of rot in mango fruits were detected, and analyzed in search of the causal agent. Concurrently, asymptomatic avocado fruits were also analyzed. The main fungal genera found, both in mango and avocado, were Alternaria sp. and Neofusicoccum sp. Of these two genera, only Neofusicoccum sp. was able to reproduce the symptoms of rot in mango like previously detected. Likewise, Neofusicoccum sp. isolates, but not Alternaria sp., could produce rot symptoms in avocado inoculated fruits. Two microbial biological control agents were tested to study the control of this disease through sustainable strategies. These candidates to biological control were Pseudomonas chlororaphis PCL1606. and Bacillus velezensis UMAF6639, both antagonists showed antifungal characteristics. The applications of both microorganisms on the fruit showed significant levels of protection during preventive applications, although only UMAF6639 showed greater persistence in the fruit during the preventive applications in the field. According to our results, it is possible to establish that pathogenic Neofusicoccum parvum and N. mediterraneum are the main causes of mango postharvest rots in southern Spain. These fungi could also be potential pathogens to avocado fruits, suggesting a risk of cross-infections among crops. Biological strategies to control postharvest rots have shown better efficacy of preventive application strategies. Following the same strategy in open field experiments.
Keywords: Mangos - Enfermedades y plagas poscosecha; Frutas - Almacenamiento - Enfermedades y daños; Botryosphaeria; Postcosecha; Mango; Aguacate